(untitled) (Research, Society and Development, 2021)
People with visual disabilities in carrying out tasks such as getting around and picking up objects face greater difficulties in supermarkets. In this respect it was noticed the lack of accessibility makes consumers with visual impairment choose to buy over the internet. In this context, we sought to explore and discuss Assistive Technology and its viability in supermarkets. The object of this work is the development of a mobile application for the supermarket, where it uses geolocation within the establishment as a means of locomotion and guidance within the supermarket, with the help of the beacon, the technology will inform the consumer where the desired product is located, in principle. what section you are in, so you can guide to the destination where the product is located. And with the Near Field Communication tags, the consumer who has visual limitation as the elderly will be able to identify which product they are taking, having knowledge: which brand, its weight, price, expiration date. For the development of the project the Ionic framework was chosen, the application has the human voice recognition mechanism, in which the visually impaired person will inform the desired product.